2021
DOI: 10.1371/journal.pone.0255698
|View full text |Cite
|
Sign up to set email alerts
|

Regional economic integration via detection of circular flow in international value-added network

Abstract: Global value chains are formed through value-added trade, and some regions promote economic integration by concluding regional trade agreements to promote these chains. However, it has not been established to quantitatively assess the scope and extent of economic integration involving various sectors in multiple countries. In this study, we used the World Input–Output Database to create a cross-border sector-wise network of trade in value-added (international value-added network) covering the period of 2000–20… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Furthermore, the years in which economic integration in the Asia-Pacific region was more advanced than in Europe were 2010 and 2013-2014 [16], the years after 2008, when the synchronization became more active. While economic integration was more than in Europe because of the decline in the extent of European economic integration after the crisis, the Asia-Pacific region was steadily increasing its economic integration.…”
Section: Synchronized Cooperative Diplomacymentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the years in which economic integration in the Asia-Pacific region was more advanced than in Europe were 2010 and 2013-2014 [16], the years after 2008, when the synchronization became more active. While economic integration was more than in Europe because of the decline in the extent of European economic integration after the crisis, the Asia-Pacific region was steadily increasing its economic integration.…”
Section: Synchronized Cooperative Diplomacymentioning
confidence: 99%
“…Some studies also sought to quantitatively measure progress in regional economic integration. Sada and Ikeda analyzed international valueadded networks created from international input-output tables and showed that there has been more substantial economic integration in the Pacific Rim than in Europe since the 2008-2009 Global Financial Crisis [16,17]. This was the result of regionalism in East Asia and the Asia-Pacific region leading to economic integration, as well as the entry into force of the mega-RTAs.…”
Section: Introductionmentioning
confidence: 99%